ChemInform Abstract: Pr1.33Pt4Ga10: Superstructure and Magnetism. Issue 46 (18th November 2014) - Doan Nguyen, Sau; Ryan, Kevin; Chai, Ping; Shatruk, Michael; Xin, Yan; Chapman, Karena W.; Chupas, Peter J.; Fronczek, Frank R.; Macaluso, Robin T.
Abstract Pr1.33Pt4Ga10 single crystals are prepared from the elements using excess Ga as flux (alumina crucible in evacuated silica ampoule, 1150 °C, 4 h, 2; ≈10% yield).